2016
DOI: 10.18805/ijar.v0iof.6664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emblica officianalis and Spirulina platensis on growth performance and serum biochemical parameters in rabbits

Abstract: The effect of Emblica officianalis and Spirulina platensis was studied in New Zealand White rabbits. Weaned rabbits of both sex were allocated to three different feeding treatments via T 1 (Control), T 2 (supplemented with 2% Emblica officianalis) and T 3 (supplemented with 5% Sprulina platensis) in addition to ad lib. berseem fodder. The concentrate diets formulated were iso-nitrogenous and iso-caloric. The final body weight, weight gain and average daily weight gain of rabbits in all the groups followed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A wellprobiotic should accelerate animal growth and improve the resistance to diseases. Besides, it should not be pathogenic and toxic, should also sustain vitality and efficiency in digestive tracks (Khanna et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A wellprobiotic should accelerate animal growth and improve the resistance to diseases. Besides, it should not be pathogenic and toxic, should also sustain vitality and efficiency in digestive tracks (Khanna et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with the finding of Abdelnour et al (2019) who supplemented rabbit diets with Chlorella vulgaris Microalgae. Also, with Peiretti and Meineri (2008), Kim et al (2010), Seyidoğlu and Galip (2013) and Khanna et al (2016) who showed that the final weight, weight gain did not differ significantly as a result of supplemented rabbit diets with Spirulina platensis microalgae. Moreover, Ayoub et al (2019) showed that supplemented Nile tilapia diets with A coffeaeformis diatoms algae with three concentration (10, 20 and 30g / kg diet) leads to enhance the growth performance, feed efficiency.…”
Section: Productive Performancementioning
confidence: 97%
“…These results are in agreement with Abdelnour et al (2019) who showed that most of the serum parameters were non-significantly different by Chlorella vulgaris microalgae supplementation in rabbit diets. Also, Seyidoğlu and Galip (2014) and Khanna et al (2016) who indicated that there were no significant changes in serum biochemical indices as a result of supplemented rabbit diets with Spirulina platensis. While there were significant decreased in triglycerides, total cholesterol and activity AST and ALT in blood plasma in Spirulina platensis microalgae groups compared to control (El-Ratel, 2017).…”
Section: Blood Metabolitesmentioning
confidence: 99%
“…and a lot of studies have been performed about the effect on life quality (Connor et al, 2007;Park et al, 2008;Khanna et al, 2016). For a good health, body weight and abdominal fat distribution are important as well as dietary fat composition.…”
Section: Splatensis Have Been Known As An Important Sourcementioning
confidence: 99%